How Sustainability Practice Shape Financial Performance in The Hospitality Industry: The Moderating Role of Firm Size - Rukmiyati, Ni Made Sri; Mareni, Ni Ketut; Tuwi, I Wayan; Arnawa, I Putu; Safitri, Ni Wayan Noviana (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study investigates the impact of energy conservation and environmental communication on the financial performance of star-rated hotels in Bali, focusing on the moderating role of firm size. SEM-PLS analysis confirms that energy conservation and environmental communication positively influence financial performance. However, firm size does not moderate the relationship between energy conservation and financial performance, but it does moderate the effect of environmental communication. These findings align with stakeholder theory, emphasizing the importance of sustainability in the hospitality industry. The study offers valuable insights for investors and regulators, recommending that they incorporate sustainability metrics into hotel investment evaluations and policy development. Hotels with strong sustainability practices, particularly in energy conservation and environmental communication, may achieve better financial performance. Investors can use these sustainability practices as part of their due diligence process. Additionally, regulators may consider implementing sustainability certification programs or incentivizing hotels that adopt such strategies. Although the study is limited to star-rated hotels in Bali, its findings lay the groundwork for future research in different regions and tourism segments. Expanding research to include various destinations and hospitality types, such as eco- resorts or airlines, can offer a broader understanding of sustainability’s financial impacts. Future studies should explore these areas to contribute to a more comprehensive understanding of how sustainability practices influence the financial performance of businesses in the global hospitality industry.